HIV-1/2 differentiation in a South African public laboratory - Rendani T. Mafuyeka; Lynne M. Webber; Piet Becker; Simnikiwe H. Mayaphi (AOSIS, 2021)
Background: The human immunodeficiency virus type-2 (HIV-2) prevalence in South Africa (SA) is unknown, however, sporadic cases have been reported. Human immunodeficiency virus -1 and 2 differentiation is not part of most South African public laboratories' testing algorithm. Human immunodeficiency virus -2 diagnosis using serology assays may be complicated by HIV-1 and HIV-2 antibody cross-reactivity. Objectives: To determine the proportion of HIV-2 infections in specimens that tested HIV-1/2 positive at a public laboratory in Tshwane. Method: A total of 480 specimens that were previously tested with fourth generation ELISA platforms (Modular E170 [Roche, Switzerland] and Architect i2000 [Abbott, Germany]) were randomly selected. Human immunodeficiency virus -1 and 2 antibody differentiation testing was carried out using the Multispot HIV-1/2 rapid assay (Bio-Rad Laboratories, USA). An in-house nested HIV-2 PCR assay targeting the 5'-long terminal repeats (5'-LTR) region was evaluated and used as a confirmatory test. Results: The study tested 480 HIV-1/2 seropositive patients and their mean age was 36.7 years (range 3-82 years). Of the 480 patients, 292 (60.8%) were female, 182 (37.9%) were male and 6 (1.3%) were not specified. Human immunodeficiency virus differentiation results were as follows: 466 (97.1%) were positive for only HIV-1 antibodies, 11 (2.3%) [95%CI: (0.98%; 3.74%)] were positive for both HIV-1 and HIV-2 antibodies, 3 (0.6%) were negative for both antibodies and none were positive for only HIV-2 antibodies. Of the 11 specimens with both HIV-1 and HIV-2 antibodies, seven had sufficient volume for confirmatory testing and were all negative on the in-house HIV-2 PCR assay. Conclusion: The multispot HIV-1/2 rapid assay demonstrated cross-reactivity between HIV-1 and HIV-2 antibodies. Human immunodeficiency virus -2 infections were not detected.